Medical students' level of competency acquisition: Assessment from teaching perspective - Guaresti, Germán (2025)
Fil: Guaresti, Germán. Universidad Nacional de Río Negro. Centro Patagónico Interdisciplinario de Investigaciones en Salud -CePIIes-Río Negro. Argentina.